2018
DOI: 10.3346/jkms.2018.33.e12
|View full text |Cite
|
Sign up to set email alerts
|

A Fast 3-Dimensional Magnetic Resonance Imaging Reconstruction for Surgical Planning of Uterine Myomectomy

Abstract: BackgroundUterine myoma is the most common benign gynecologic tumor in reproductive-aged women. During myomectomy for women who want to preserve fertility, it is advisable to detect and remove all myomas to decrease the risk of additional surgery. However, finding myomas during surgery is often challenging, especially for deep-seated myomas. Therefore, three-dimensional (3D) preoperative localization of myomas can be helpful for the surgical planning for myomectomy. However, the previously reported manual 3D s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…Gradual developments in CT and MRI technology and software allowed these examinations to be used in DFSP patients. Nowadays, 3D reconstruction models based on CT and MRI data are used to construct the tridimensional structure of tumors and organs [ 20 22 ]. As a result, we elected to design 3D DFSP reconstruction models, which were really useful: First, 3D tumor models made it possible to generate a precise size and configuration to define the tumor boundaries, particularly the depth of invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Gradual developments in CT and MRI technology and software allowed these examinations to be used in DFSP patients. Nowadays, 3D reconstruction models based on CT and MRI data are used to construct the tridimensional structure of tumors and organs [ 20 22 ]. As a result, we elected to design 3D DFSP reconstruction models, which were really useful: First, 3D tumor models made it possible to generate a precise size and configuration to define the tumor boundaries, particularly the depth of invasion.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a growing number of studies reported the benefits of HA3D in preoperative surgical planning and intraoperative guidance in non-gynaecological procedures (Tsaturyan et al,2021;Porpiglia et al, 2018;Porpiglia et al, 2019). However, only a few studies have described the 3D imaging technique feasibility in the gynaecological field (Lee et al, 2018;Aluwee et al, 2015). To the best of our knowledge, this is the first video-article describing the use of HA3D imaging technology in gynaecologic surgery.…”
Section: Discussionmentioning
confidence: 92%
“…With advances in MRI, unprecedented levels of anatomical detail can be reached with many applications. The creation of 3D models through segmenting and merging images can offer an improved signal-to-noise ratio over planar imaging and help overcome artefact interference [ 26 ]. 3D reconstruction of fibroid position for surgical planning has been reported [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The creation of 3D models through segmenting and merging images can offer an improved signal-to-noise ratio over planar imaging and help overcome artefact interference [ 26 ]. 3D reconstruction of fibroid position for surgical planning has been reported [ 26 ]. However, the study by Lee et al, was focused on localisation on a 3D gird principle.…”
Section: Discussionmentioning
confidence: 99%